Sustainable Futures: Exploring Cenderawasih Bay National Park as Indonesia’s Emerging Ecotourism Hub through Life Cycle Sustainability Assessment and Green Theory - Putra, Ketut Candra Pangestu; Aurani Azalia Putri; Rifqi Dirga Syahputra (WIMAYA, 2023)
This study examined the potential for ecotourism development centered around whale sharks in Cenderawasih Bay National Park. The preservation of Cenderawasih Bay National Park has been officially recognized as a national park and was regarded as a crucial conservation priority in Indonesia. Nonetheless, distinct obstructions and complexities were present during the execution of whale shark ecotourism in Cenderawasih Bay National Park. The implementation necessitated a careful and conscientious approach that adhered to the tenets of responsible and sustainable ecotourism. This research utilized the Life Cycle Sustainability Assessment (LCSA) and Green Theory to examine the ecological, social, and economic implications of the whale shark ecotourism sector in Cenderawasih Bay National Park comprehensively and sustainably. By integrating these two approaches, this research aimed to offer all-encompassing and enduring strategic suggestions for advancing whale shark ecotourism in Cenderawasih Bay National Park.